Crumbs promotes expanded recognition and degradation by the SCF(Slimb/β-TrCP) ubiquitin ligase - Ribeiro, Paulo (National Academy of Sciences, 2014)
In epithelial tissues, growth control depends on the maintenance of proper architecture through apicobasal polarity and cell–cell contacts. The Hippo signaling pathway has been proposed to sense tissue architecture and cell density via an intimate coupling with the polarity and cell contact machineries. The apical polarity protein Crumbs (Crb) controls the activity of Yorkie (Yki)/Yes-activated protein, the progrowth target of the Hippo pathway core kinase cassette, both in flies and mammals. The apically localized Four-point-one, Ezrin, Radixin, Moesin domain protein Expanded (Ex) regulates Yki by promoting activation of the kinase cascade and by directly tethering Yki to the plasma membrane. Crb interacts with Ex and promotes its apical localization, thereby linking cell polarity with Hippo signaling. We show that, as well as repressing Yki by recruiting Ex to the apical membrane, Crb promotes phosphorylation-dependent ubiquitin-mediated degradation of Ex. We identify Skp/Cullin/F-box(Slimb/β-transducin repeats-containing protein) (SCF(Slimb/β-TrCP)) as the E3 ubiquitin ligase complex responsible for Ex degradation. Thus, Crb is part of a homeostatic mechanism that promotes Ex inhibition of Yki, but also limits Ex activity by inducing its degradation, allowing precise tuning of Yki function.